Post-Gen Z Protests and Federal Security: Implications for Institutions and Policy in Nepal (Prashasan: The Nepalese Journal of Public Administration, 2025)
Nepal’s national security landscape has undergone a profound transformation following federal restructuring, geopolitical shifts, demographic mobility, rising cyber vulnerabilities, and the youth-driven Gen Z movement, which challenged state authority and affected the morale of security institutions. This article provides a multi-dimensional, research-based assessment of Nepal’s national security architecture grounded in doctrinal, institutional, and operational perspectives. It analyzes immigration security, citizenship governance, electoral vulnerabilities, federal coordination failures, border management gaps, security-sector morale, and strategic intelligence weaknesses. Building on scholarly frameworks of human security, hybrid threats, and civil-military relations, the study proposes a comprehensive national security reform pathway aligned with Nepal’s constitutional, geopolitical, and socio-technological realities. The analysis draws from constitutional provisions, security doctrines, existing policies, regional security studies, and contemporary political events.